'The space that divides and connects.' Betweenness and the intersubjective perspective. Issue 1 (2nd January 2018) - Pitruzzella, Salvo
Abstract : In my opinion, the most important aspect of Roger Grainger's legacy is that his many books and articles are not only a guide to understand the meaning of dramatherapy, but also a vast inquiry on human nature, as well as a hymn of joy for what such a nature is, with its bliss and its misery. My ideas about what dramatherapy is are largely inspired from his thought, yet I reckon that my understanding of how it works derives primarily from my experiences of live meetings with him. Therefore in this article, which will mingle personal feelings with theoretical considerations, I will recall some of the encounters I had with him.